Violent behaviour and posttraumatic stress disorder - Begić, Dražen (Array, 2002)
Future research into violent behaviour and post-traumatic stress disorder will reveal the risk factors for this disorder, and try to explain what it is that, afterexposing an individual to psychological trauma, leads to post-traumatic stress disorder. Possible protective factors and mechanisms to prevent the occurence of post-traumatic stress disorder will be described.